2019
DOI: 10.1007/s00345-019-02825-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of alcohol consumption on the risk of developing bladder cancer: a systematic review and meta-analysis

Abstract: Background Epidemiologic studies that investigated alcohol consumption in relation to the risk of bladder cancer (BCa) have demonstrated inconsistent results. We conducted a systematic review and meta-analysis of the literature to investigate the association of alcohol including different types of alcoholic beverages consumption with the risk of BCa. Materials and methods A systematic search of Web of Science, Medline/PubMed and Cochrane library was performed in May 2018. Studies were considered eligible if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…green tea (57) ) and beverages with a potential harmful effect on BC risk (e.g. alcoholic (58) and sweet nonalcoholic beverages (43) ). It, therefore, remains unclear which caused the observed increased BC risk.…”
Section: Discussionmentioning
confidence: 99%
“…green tea (57) ) and beverages with a potential harmful effect on BC risk (e.g. alcoholic (58) and sweet nonalcoholic beverages (43) ). It, therefore, remains unclear which caused the observed increased BC risk.…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese have a higher prevalence of polymorphisms in the aldehyde dehydrogenase 2 (ALDH2) enzyme, which makes them slower at metabolizing acetaldehyde . Previous studies have indeed suggested an elevated cancer risk from alcohol consumption in the urinary tract and prostate in Japan, which has not been found in Western countries . We have hypothesized that there may be an elevated cancer risk at even light to moderate levels of alcohol consumption in Japan due to a higher prevalence of ALDH2 polymorphisms in the Japanese.…”
Section: Introductionmentioning
confidence: 94%
“…9,14 Previous studies have indeed suggested an elevated cancer risk from alcohol consumption in the urinary tract and prostate in Japan, which has not been found in Western countries. 9,10,[15][16][17][18][19] We have hypothesized that there may be an elevated cancer risk at even light to moderate levels of alcohol consumption in Japan due to a higher prevalence of ALDH2 polymorphisms in the Japanese.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cigarette smoking increases the risk of recurrence and progression of non-muscle-invasive bladder cancer (NMIBC) [10]. Alcohol consumption may also increase the risk of UCB, particularly in males [11]. The presence of SNPs in key DNA repair pathways that are involved in the response to DNA damage caused by these environmental carcinogens, including the nucleotide excision repair (NER) and the homologous recombination repair (HRR) pathways, may increase the risk of developing UCB [6,12].…”
Section: Introductionmentioning
confidence: 99%